The Impact of Revenue Diversification on Bank Performance and Risk: Evidence from Bangladesh - Sany, Md. Aminul Islam; Lata, Rabeya Sultana (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study examines whether revenue diversification improves or harms banks' profitability and financial stability in Bangladesh. Method: A panel dataset covering 270 observations from DSE-listed banks spanning 2014 to 2023 is used. This study applies fixed-effects and random-effects regression models using STATA 13. Key performance indicators such as Return on Assets (ROA), Return on Equity (ROE), and Z-score (a measure of financial risk) are analyzed. The control variables include bank size, leverage, asset growth, the deposit-to-total-assets ratio, and macroeconomic indicators such as GDP growth and inflation. Results: Revenue diversification negatively impacts profitability and financial stability. ROA, ROE, and Z-score have significantly negative relationships with revenue diversification. Larger banks tend to be less profitable and stable, whereas a higher deposit-to-total-assets ratio improves performance. GDP growth has a slight positive impact on profitability but does not significantly affect the financial stability. Conclusions: Diversifying income sources may not always benefit Bangladeshi banks. This can reduce profitability and increase financial risk. Managing leverage and improving asset utilization are crucial for achieving better financial outcomes. Limitations: This study is limited to DSE-listed banks in Bangladesh and does not consider unlisted banks or non-bank financial institutions in its analysis. Contribution: This study contributes to the banking and finance field by offering insights into the effects of revenue diversification on bank performance and risk in a developing economy. This can help policymakers, bank managers, and financial analysts make better decisions regarding income strategies and risk management.